Efficacy of therapeutic ultrasound with soft tissue mobilization in patients of oral submucous fibrosis - Himani Tyagi; Manisha Lakhanpal; Manu Dhillon; Apala Baduni; Anchal Goel; Akansha Banga (Wolters Kluwer Medknow Publications, 2018)
Aims: To study the effect of adjuvant therapeutic ultrasound with soft tissue mobilization in the management of patients suffering from oral submucous fibrosis (OSMF). Settings and Design: This study was conducted on OSMF patients visiting the outpatient department of Oral Medicine and Radiology, ITS-CDSR, Muradnagar, Ghaziabad, in collaboration with Physiotherapy Department ITS CDSR. Materials and Methods: Thirty patients diagnosed clinically and histopathologically with OSMF were enrolled in the study. They were divided into two groups consisting 15 patients each in group A and group B.Both A and B groups were given lycopene (12mg/day) and intralesional (I/L) injection (biweekly) for 3 months. Therapeutic ultrasound with soft tissue mobilization was used only in group B. Statistical Analysis Used: An independent t-test was done for intergroup comparison for group 1 and group 2. Results: Two groups show that the difference in the treatment in both the group was highly significant at >0.01 to very highly significant at 0.001. Itshowsthat in group A, the effect is steady, and in group B, the effect is substantialwithin the first 15 days; nevertheless, the total clinical effect after 3 months is similar in both the groups. Conclusions: Therapeutic ultrasound when used as an adjuvant shows a significant improvement in the patient's condition with no reported side effects. Hence, should be incorporated in the treatment protocol for patients with OSMF.